Research on a public-private partnership scheme for space industry creation - Shinichi TAKATA; Kazuyoshi HIDAKA (Nihon Kikai Gakkai ronbunshu)
The purpose of this paper is to present a new open innovation type public-private partnership scheme in the space sector, which is suitable for the space industrial complex in Japan, to promote R&D and to realize national projects by public R&D agencies, and to create commercial business by private companies simultaneously. Compared to other sectors, system development and business creation in the space sector remains difficult. Then typical public-private partnership methods from other industries cannot be applied to the space sector, although the U.S. and other countries are promoting public-private partnerships in the space sector. And the more private sector support is provided, the more it will affect the R&D capabilities of public R&D space agencies. Furthermore, Japan has a large gap with the U.S. in terms of technological infrastructure and budget, making it difficult to apply the space public-private partnership methods of the U.S. The scheme proposed in this paper is based on a technology-circulating collaboration model applicable to the Japanese machinery manufacturing industry in general, with modifications to adapt it to the space industrial complex in Japan and to help solve the above issues. Then, a case study analysis is presented to illustrate the suitability of this scheme.